ANALISIS PORTOFOLIO SEBAGAI DASAR PENGAMBILAN KEPUTUSAN INVESTASI SAHAM YANG TERDAFTAR PADA BURSA EFEK INDONESIA (BEI) (Studi pengunaan Model Indeks Tunggal pada saham yang terdaftar di LQ45 Periode Februari 2014 s.d Juni 2015 ) - astawinetu, erwin dyah; fitriyah, lailatul (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACTThis study aims to determine the optimal shares listed on the Indonesia Stock Exchange (IDX) contained in LQ45 using the method of single index model. This research is a descriptive study, the method used is quantitative method. Samples were taken at thirty-six shares of the company from LQ45 period February 2014 to June 2015. The samples were taken using purposive sampling technique. Results from this research that showed that out of thirty-six stock companies only two shares optimal namely PT. Gudang Garam Tbk. (GGRM) and PT. AKR Corporindo Tbk. (AKRA). With the proportion of funds PT. Gudang Garam Tbk. (GGRM) of 0.6624, while PT PT. AKR Corporindo Tbk. (AKRA) of 0.3376. In addition the rate of return from the formation of the portfolio is equal to 0.0084 at the risk of the portfolio amounted to 0.000017 smaller than market risk amounted to 0.001404. This proves that the establishment of a portfolio would gain optimal benefit with certain risk. Keywords: Optimal Portfolio, Single Index Model, risk, rate of return.